Contemporary consumption, consumers and marketing : cases from generations Y and Z - Canavan, Brendan (Abingdon ; New York : Routledge, 2021)
"This book explores current consumer, consumption and marketing cases and issues, posing questions that complement, extend and challenge established marketing theory. Coming of age in a volatile, uncertain, complex and ambiguous context, members of generations Y and Z are emerging as distinctive and disruptive in terms of their identities, attitudes, and their consumption. Challenged by demanding consumers, facing ideological backlash, and worse, potential irrelevance, marketers need to gain a sense of the issues currently rocking consumer culture. Contemporary Consumption, Consumers and Marketing captures examples of contemporary consumers using up-to-date case studies that demonstrate divergent trends across Generations X, Y and Z. From BrewDog's craft beer revolution, to Taylor Swift socially reconstructing herself lyrically, through RuPaul stans flexing their inventiveness online, and Japanese Otaku retreating into alternative reality, these are reviewed to investigate the state of marketing at a time of flux. The aim is to engage readers in the dynamic global changes happening in marketing theory and practice. The result is a thought provoking and stimulating text for undergraduate and postgraduate marketing students"--
OCLC-licensed vendor bibliographic record.
Keywords: Consumption (Economics); Consumers' preferences; Branding (Marketing); Generation Y -- Attitudes; Generation Z -- Attitudes; BUSINESS & ECONOMICS / Marketing / Direct; BUSINESS & ECONOMICS / Consumer Behavior